2010
DOI: 10.1111/j.1556-4029.2009.01217.x
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Imaging of Latent Fingerprints by Localized Corrosion on Brass Surfaces

Abstract: The Atomic Force Microscope (AFM) is capable of imaging fingerprint ridges on polished brass substrates at an unprecedented level of detail. While exposure to elevated humidity at ambient or slightly raised temperatures does not change the image appreciably, subsequent brief heating in a flame results in complete loss of the sweat deposit and the appearance of pits and trenches. Localized elemental analysis (using EDAX, coupled with SEM imaging) shows the presence of the constituents of salt in the initial dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…Accordingly, and in light of topical forensic concerns, the study of S 2 N 2 interaction with cleaned fingermarks on metal surfaces, became paramount. 5 In contrast to standard chemical fingerprint detection techniques, the key feature of the results presented here is that even when the print is no longer chemically present, interaction with S 2 N 2 persists via the print's corrosive modification of the surface; crucially, this occurs even when 10 the print has had a relatively short time to manifest the corrosion. Figure 1 shows this effect in practice ‡ on brass plates.…”
Section: Heatmentioning
confidence: 90%
See 2 more Smart Citations
“…Accordingly, and in light of topical forensic concerns, the study of S 2 N 2 interaction with cleaned fingermarks on metal surfaces, became paramount. 5 In contrast to standard chemical fingerprint detection techniques, the key feature of the results presented here is that even when the print is no longer chemically present, interaction with S 2 N 2 persists via the print's corrosive modification of the surface; crucially, this occurs even when 10 the print has had a relatively short time to manifest the corrosion. Figure 1 shows this effect in practice ‡ on brass plates.…”
Section: Heatmentioning
confidence: 90%
“…Pioneering 35 work by Bond 10 and Williams 11 has revealed that instrumental techniques such as Atomic Force Microscopy and Scanning Kelvin Probe can image the minuscule surface corrosion effect generated by prints which have been laid down on metallic surfaces, even after the prints themselves have been 40 removed through various rigorous cleaning regimes. These results highlight the immense potential of such minor corrosive action on forensically pertinent substrates; however, the imaging techniques themselves suffer realistic limitations, such as the length of time required to process a macroscopic 45 area, cost and problems analysing irregular surface forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main advantages of this method are simplicity and low costs for instrumentation and reagents. Several approaches based on corrosion have been presented by Bond et al [3,4,5,6,7,8]. In [4] the authors evaluated the corrosion characteristics of latent fingerprints using ten metal elements and ten metal alloys.…”
Section: Related Workmentioning
confidence: 98%
“…Bottom-up nanotechnology has been useful in imaging latent fingerprint corrosion on fired brass [14] shell casings [15] that is enhanced by the presence of aqueous electrolytes [16] (e.g. Cl À in eccrine sweat), i.e.…”
Section: Introductionmentioning
confidence: 99%